Balancing debt with sustainability? Fiscal policy and the future of petroleum revenue management in Ghana. (September 2020) - Ackah, Ishmael; Bobio, Crispin; Graham, Emmanuel; Oppong, Charles Kwadwo
Abstract: Among other things, sustainable development requires that countries prepare for the future. This requirement was not lost on policymakers in Ghana when both the Petroleum Revenue Management Act (PRMA) and public financial management laws were being prepared. In the PRMA for instance, a stabilisation fund has been created. The stabilisation fund has two main goals. The first is to cushion government expenditure during oil price fall. Second, excess from the cap of the stabilisation fund is transferred to the Sinking Fund for debt repayment. Similarly, there is a heritage fund, which serves as an endowment for future generations. Despite these funds and the implementation of a diversification strategy, it has been observed, Ghana is characterised by high budget deficits and borrowing levels. This study analysed data from the Bank of Ghana and the Ministry of Finance to ascertain whether the purpose for which these fiscal measures were put in place have been achieved. The findings show that oil production has not done much to ensure fiscal discipline and reduce the budget deficit. In addition, while the share of oil revenues in total domestic revenues has been rising, domestic revenues as a proportion of GDP has remained stagnant whilst debt policy rating has deteriorated. Instead of complementing, oil revenues may be replacing other sources of revenue.